Influence of Sex and Age on Depression among First Year Undergraduates of Faculty of Education in Cross River State, Nigeria - Njoku, Joy Nwaobiara; Igbodor, David Onwe; Amalu, Melvina N. (Richtmann Publishing, 2020)
This study was on the influence of sex and age on depression among first year undergraduates in Cross River State, Nigeria. The population of the study was 2,800 first year students of the two Universities in Cross River State (University of Calabar and Cross River State University of Science and Technology). A sample of 560 first year students was drawn from the institutions to take part in the study using random sampling technique. This comprised of 269 males and 291 females. A questionnaire with two sections was used for data collection. Section A, elicited responses for sex and age while section B was an adapted Beck’s depression inventory to gather information on the degree of depression among the students. The statistical tools used were the independent t-test and ANOVA. T-test was used to analyze responses on sex while the ANOVA was used to analyze responses on age and depression. The results showed that the males were more depressed than the females and depression also increased with age.It was recommended among other things that parents and sponsors of these students should show equal care in terms of giving upkeep money to both the males and the females. People should also be encouraged to go to school at early age.